The gendered impact of COVID-19 on FGM: 2021 Prize WinnerWe are delighted to announce the winner of our 2021 Practitioner and Early Career Researcher Prize in the category of COVID-19: Ottis Mubaiwa, Tamsin Bradley, and Jane Meme, "The Gendered Impact of COVID-19 on Female Genital Mutilation (FGM)" (forthcoming, 32.6, 2022). This important article reveals how the COVID-19 lockdowns have had a devastating impact on gender-based violence in Somalia/Somaliland, Ethiopia, and Kenya. The article draws attention to the urgent need for the integration of responses to FGM, and other forms of violence against women and girls, as part – of the development response to pandemics. Issue 6 (18th August 2022) - Mubaiwa, Ottis; Bradley, Tamsin; Meme, Jane
ABSTRACT: The gendered impact of the COVID-19 pandemic on women and girls has deepened pre-existing gender inequalities and gender-based violence. Research conducted between February and May 2021 with partner organisations in Somalia/Somaliland, Ethiopia, and Kenya was able to add more evidence to the growing acknowledgement that COVID-19 has triggered an increase in the prevalence of FGM. Furthermore, the research highlighted the urgent need for responses to FGM and other forms of violence against women and girls to be integrated as part of the development response to pandemics. The article points to a need to look more closely at how and why changes in harmful mindsets happen. The findings reveal that unless change is triggered by strong convictions to respect the rights of girls, it is highly fragile and unlikely to be sustained.